Plant Extracts as Alternative Additives for Sperm Preservation - José Luis Ros-Santaella; Eliana Pintus (MDPI AG, 2021)
Sperm preservation is a crucial factor for the success of assisted reproductive technology (ART) in humans, livestock, and wildlife. Irrespective of the extender and the storage conditions used, semen handling and preservation negatively affect sperm quality. Moreover, oxidative stress, which often arises during semen storage, significantly reduces sperm function and compromises the sperm fertilizing ability by inducing oxidative damage to proteins, lipids, and nucleic acids. Plant extracts have recently emerged as a cheap and natural source of additives to preserve and enhance sperm function during semen storage. The present work provides an update on the use of these natural compounds as alternative additives for sperm preservation in 13 animal species, including humans. A detailed description of the effects of 45 plant species, belonging to 28 families, on sperm function during semen storage is presented. The plant material and extraction method employed, dosage, possible toxic effects, and antimicrobial properties are provided.